Antibacterial and Antitumor Activities of Biscoumarin and Dihydropyran Derivatives - Yun-Peng Sui; Hai-Ru Huo; Jia-Jia Xin; Jing Li; Xiao-Jun Li; Xin-Liang Du; Hai Ma; Hai-Yu Zhou; Hong-Dan Zhan; Zhu-Ju Wang; Chun Li; Feng Sui; et al. (Molecules, 2015)
A novel series of biscoumarin (1–4) and dihydropyran (5–13) derivatives were synthesized via a one-pot multicomponent condensation reaction and evaluated for antibacterial and antitumor activity in vitro. The X-ray crystal structure analysis of four representative compounds, 3, 7, 9 and 11, confirmed the structures of these compounds. Compounds 1–4 showed the most potent antitumor activity among the total 13 derivatives; especially for compounds 1 and 2, they also emerged as promising antibacterial members with better antibacterial activity. In addition, the results of density functional theory (DFT) showed that compared with compounds 3 and 4, biscoumarins 1 and 2 had lower intramolecular hydrogen bonds (HB) energy in their structures.